Increased Levels of Brain-Derived Neurotrophic Factor Are Associated With High Intrinsic Religiosity Among Depressed Inpatients - Mosqueiro, Bruno Paz; Fleck, Marcelo P.; Rocha, Neusa Sica da (Frontiers in Psychiatry, 2019)
Recognition of the importance of religion and spirituality in psychiatry is increasing, and several studies have shown a predominantly inverse relationship between religiosity and depression. Brain-derived neurotrophic factor (BDNF) is a widely studied brain neurotrophin responsible for synaptic plasticity, dendritic and neuronal fiber growth, and neuronal survival. The objective of the present study was to evaluate BDNF levels across high and low intrinsic religiosity (IR) in depressed inpatients. Serum BDNF levels were evaluated from 101 depressed inpatients at hospital admission and 91 inpatients at discharge. Religiosity was assessed using a validated version of the Duke University Religion Index. High IR patients had significantly higher serum BDNF at discharge compared to low IR (52.0 versus 41.3 ng/mL, P = 0.02), with a Cohen’s d effect size difference of 0.56. High IR patients had a statistically significant increase in BDNF levels from admission to discharge (43.6 ± 22.4 versus 53.8 ± 20.6 ng/mL, -1.950 (paired t-statistic), P = 0.05). The relationship between IR and BDNF levels (F=6.199, p=0.00), was controlled for the effects of depressive symptoms (β = 2.73, P = 0.00) and psychiatric treatments, including SSRI (β = 0.17, P = 0.08), SNRI (β = -0.23, P = 0.02), TCA (β = -0.17, P = 0.10), lithium (β = 0.29, P = 0.00), anticonvulsants (β = 0.22, P = 0.03), antipsychotics (β = -0.05, P = 0.61), and electroconvulsive therapy (β = 0.00, P = 0.98). The current findings suggest a potential pathway to help understand the protective effect of religiosity in depressive disorders.